DETERMINANTS OF BOWEL RESECTION IN CHILDHOOD INTUSSUSCEPTION - Nisar, Muhammad Umar; Sikander, Samer; Khan, Nisar Ahmed; Javed, Noshela; Chaudhary, Muhammad Amjad; Saif, Mohammed Abdulmomen Abdullah (Journal of Ayub Medical College Abbottabad, 2020)
Background: Intussusception is an acute surgical emergency and one of the most common causes of acute abdomen in early paediatric age group with peak incidence between 3 months to 3 years. It is considered the most common cause of intestinal obstruction in first two years of life. Early diagnosis and management may prevent major complications of bowel ischemia and necrosis thus avoiding morbidity and mortality. Our objective was to evaluate the risk factors or determinants of bowel resection in childhood intussusception. Methods: It is a prospective, descriptive and cross-sectional study in which 102 consecutive cases of intussusception presenting to The Children's Hospital PIMS, from January 2018 to May 2019, were included. Results: Total 102 patients were included in the study. Seventy-three (71.6%) were male and 29 (28.4%) were female. Mean age at presentation was 16.30 months (ranged from 1 day to 9 years). Mean duration of symptoms was 3.1 days. 52.9% (53/102) patients had mass palpable on abdominal examination while 22.5% (23/102) had palpable mass on digital rectal examination (DRE). Mean haemoglobin at presentation was 10.2 g/dL (min 4g/dL, max 26g/dL) and mean haematocrit was 32.6 %. The most common type of intussusception was ileo-colic (57.8%) followed by ileo-ileal (21.6%). 36.3% (37/102) patients had to undergo bowel resection due to bowel gangrene/necrosis while in 66 (64.7%) patients had manual reduction. Statistically significant relationship was found between resection and duration of symptoms more than 24 hours (p=0.01, CI=95% OR= 6.24), haemoglobin less than 10g/dL (p=0.022, CI=95% OR=2.78) and haematocrit less than 30% (p=0.028, CI=95% OR=2.63). Conclusion: Prevention of anaemia and early presentation to a facility where trained paediatric surgeons are available can reduce the chances of bowel resection in childhood intussusception. Keywords: Intussusception; Paediatric age; Risk factors; Intestinal viability; Intestinal necrosis; Pakistan